High frequency of benzimidazole resistance polymorphisms and age-class differences in trichostrongyle nematodes of ranched bison from the south-central United States - Kaylee R. Kipp; Elizabeth M. Redman; Joe L. Luksovsky; Dani Claussen; John S. Gilleard; Guilherme G. Verocai (International Journal for Parasitology: Drugs and Drug Resistance)
Bison production is a growing sector of the United States agriculture, with more consumers choosing bison products. Commercial bison are kept on smaller pastures and treated with anthelmintics for gastrointestinal nematodes (GIN) to maintain production. However, there is a lack of information regarding the GIN parasite communities in ranched bison or the extent of their resistance to anthelmintics. Our objectives were: i) to determine the GIN species present and the extent of resistance to the benzimidazole drug class in commercial bison herds in the southern US and ii) to assess age class differences in GIN species composition and BZ resistance. Composite coprocultures from bison in Texas (n = 14) and Oklahoma (n = 2), and individual bison of different age classes from a single ranch in central Texas (n = 43) were analyzed using ITS2 rDNA nemabiome metabarcoding to determine the trichostrongylid species composition. For both the composite and individual samples, the most common trichostrongylid species found were Haemonchus contortus, Haemonchus placei, and Ostertagia ostertagi. Among the known canonical isotype-1 β-tubulin BZ resistance polymorphisms (at codons 200, 198, 167), the 200Y (TTC > TAC) substitution was the most widespread across the two southern states, with a prevalence of 81.3 %. Other polymorphisms, such as 167Y (TTC > TAC) and 198L (GAA > TTA), were also detected, and both had prevalences of 62.5 %. Ostertagia ostertagi was found to have very high frequencies (overall mean frequency = 62.6 %; range = 28.3–100 %) of the 200Y (TTC > TAC) polymorphism in all age classes sampled. Overall, benzimidazole resistance polymorphisms were found at moderate to high frequency in the three major economically important GIN species in ranched bison in Texas and Oklahoma, suggesting a potential widespread distribution of benzimidazole resistance polymorphisms in the southern United States. This work has important implications for all other grazing livestock and illustrates the importance of early detection of anthelmintic resistance and the need for mitigation strategies.